TENSIONS OF CHURCH T(T)RADITION AND THE AFRICAN TRADITIONAL CULTURES IN THE AFRICAN ORTHODOX CHURCH OF KENYA: JUSTIFYING CONTEXTUALIZATION - THIANI , Evangelos (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2020)
The African Orthodox Church of Kenya was formed as an African Instituted Church in 1929, with considerable cultural and liberative connotations, before officially joining the Greek Orthodox Patriarchate of Alexandria and All Africa in 1956. The journey of being faithful to the rich and ancient Eastern Orthodox tradition, history, and heritage as well as grappling with the local cultures is been an ongoing tension for this church. The tension is better appreciated from the eye view of non-Kenyan Orthodox and young theologians in comparison with that of the locals. Some contextualization practices within this church were ecclesiastically sanctioned, while others have never been reviewed, even though both are practiced with no distinction. This Orthodox Church in Kenya continues to be regarded as one of the staunchest and first growing Orthodox Church in Africa, influencing many upcoming African dioceses and the theologians they form in the main Patriarchal seminary based in Nairobi. This paper seeks to document this tension and struggle of the church and local community traditions and cultures, and with it seek to justify some of the contextualization that is realized and practiced in this church at present.